Critical Factors Influencing the Success of Social Entrepreneurship - Nepal, Achyut (Journal of Advanced Academic Research, 2024)
Social entrepreneurs are solving agents for social and economic problems. Having innovations aimed to tackle the unlimited human problems innovators enter into the business as social entrepreneurs. Putting independent scientific findings into the practical field of business poses several problems requiring the entrepreneur to tackle the issues and challenges of the business world. This study aimed to answer the linkage of innovation with social entrepreneurship, the relation of individual innovators with entrepreneurship, types of the support the society can provide to social entrepreneurs in their contribution to solving the unlimited human problems, and the role of political economy in achieving success by social entrepreneurs. The methodology employed for the study involves a review of the findings of previous studies and an analysis of the opinions of the leading social entrepreneurs. The main finding of the study includes an educational program to clarify the duality of the understanding of social entrepreneurship, preparation, and implementation of robust business strategy along with identification of market relevance of innovation, innovative funding of start-up and scaling stage of entrepreneurship, perpetuity in innovation for sustainability, friendly public policy and public sector as a potential partner in achieving success of social entrepreneurship as the critical factors.